Gambaran Pengetahuan Gizi dan Sikap Remaja Putri terhadap Kepatuhan Mengkonsumsi Tablet Tambah Darah di SMA Negeri 6 Palembang - Rosenda, Caroline; Wiyanti, Sri; Siregar, Afriyana (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2023)
Background : Young women are a group that is prone to anemia because they are easily influenced by the social environment including food selection.9) The impact on young women is a decrease in learning concentration so that they can experience bleeding before and during childbirth. Purpose of the study was to determine the picture of nutritional knowledge and attitudes of adolescent girls towards adherence to taking blood-added tablets at SMA Negeri 6 Palembang. Method is discriptive with a cross sectional design. The sample used was 70 young women in class XI MIPA and Social Studies. For sampling techniques using proportional stratified random sampling and simple random sampling with analysis data using univariate and bivariate analysis. Results: this study showed that 64 people (91.4%) of adolescent girls with non-compliance knowledge and 55 women (78.6%). Conclusion: From the cross-table analysis, adherence of adolescent girls taking TTD (Blood Added Tablets) both has nutritional knowledge as many as 15 people (23.4%) and admonition of adolescent girls with good attitudes as many as 11 people (55%) in taking blood added tablets. Suggestion: based on the results of this study, it is hoped that adolescent girls realize that taking TTD can minimize anemia and as a preparation for the future before becoming a mother.